Ultrastructural aspects of equine exertional rhabdomyolysis - Sucre, Luis Eduardo; Finol, Héctor José; Thompson, Kent (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
An electron microscope study was carried out with left Gluteus medius muscle samples, of fifty-one (51) mares (3-4 years old). Sixteen (16) of these were inactive (approximately 4 months), and with no signs or symptoms of exertional rhabdomyolysis ER (control group), the other thirty-five (35) mares with (ER), were in training at the “La Rinconada” Racetrack (Caracas-Venezuela). Fifteen (15) had sub-clinical phases of the disease, three (3) showed clinical episodes, and seventeen (17) showed recent episodes (approximately 8 days) of ER (chronic periods of the syndrome). Three phases of the process were observed in the left Gluteus medius muscle: Phase 1 atrophy, phase 2 segmental necrosis and phase 3 regeneration. In some cases all three phases were found in the same animal. Ultra-structural aspects of these three phases are discussed and related to some possible etiologic mechanisms.